2001
DOI: 10.1007/s004640090073
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic transperitoneal hernia repair of incarcerated hernias: Is it feasible?

Abstract: Laparoscopic inguinal hernia repair (TAPP) represents an efficient therapeutic concept in the treatment of both chronically and acutely incarcerated inguinal hernias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(62 citation statements)
references
References 10 publications
4
52
0
6
Order By: Relevance
“…According to expert opinion, TEP may be advantageous in connection with direct hernias, especially in bilateral locations, but indirect hernias-and especially large hernias (scrotal)-may be more easily operated on using TAPP (level 5). Moreover, experts agree that TAPP is better in patients with a strangulated hernia [29], in patients with a recurrence after previous preperitoneal repair [32], and in hernia patients with a history of previous radical transabdominal prostatectomy [31] (level 5).…”
Section: Comparison Of Tapp and Tepmentioning
confidence: 97%
See 1 more Smart Citation
“…According to expert opinion, TEP may be advantageous in connection with direct hernias, especially in bilateral locations, but indirect hernias-and especially large hernias (scrotal)-may be more easily operated on using TAPP (level 5). Moreover, experts agree that TAPP is better in patients with a strangulated hernia [29], in patients with a recurrence after previous preperitoneal repair [32], and in hernia patients with a history of previous radical transabdominal prostatectomy [31] (level 5).…”
Section: Comparison Of Tapp and Tepmentioning
confidence: 97%
“…In these studies it was clearly demonstrated that in experienced hands, both TAPP and TEP are safe and effective techniques for treatment of inguinal hernia. Moreover, it was shown that all types of inguinal hernia can be successfully treated with TAPP [25], even the most complicated cases: strangulated hernias [29], scrotal hernias [30], hernias after radical transabdominal prostatectomy [31], and recurrences after previous preperitoneal repair [32]. Furthermore, the outcomes of patients who have undergone TAPP for bilateral hernia are in no way worse than after repair of a unilateral hernia [33].…”
Section: Grades Of Recommendationmentioning
confidence: 99%
“…Incarcerated hernia has been among the last of the hernia types to be treated laparoscopically. The procedure still is controversial, and may be contraindicated in some cases [20], but successful reduction and repair have been reported for nonacutely incarcerated inguinal hernia [5,8,14]. Of the few studies available, most involve use of the transabdominal approach (TAPP) [5,12,14,27].…”
Section: Introductionmentioning
confidence: 99%
“…It reviews seven articles on this topic, dating from 1989 to 2008, reporting on 328 cases treated with total extraperitoneal (TEP) or transabdominal preperitoneal (TAPP) repair. Of these seven articles, two are LE 2b prospective cohort studies and five are LE 4 small case series [271][272][273][274][275][276][277]. The overall results of the Deeba et al study were that average operative time was 61.3 min, average hospital stay was 3.8 days, mortality rate was 0.28 %, complication rate was 10.3 %, conversion rate was 1.8 %, intestinal laparoscopic or minilaparotomy resection rate was 5.1 %, and reoperation rate was 0.9 %.…”
Section: Incarcerated/strangulated Herniasmentioning
confidence: 99%